Evolutionary and functional epitopes of the Spätzle protein: new insights into activation of the Toll receptor. - Wang, Y.; Zhu, S. (Cellular and molecular life sciences. CMLS, 2009)
Spätzle, a dimeric ligand, binds to the Drosophila Toll receptor and activates the signal pathway functioning in both embryonic patterning and innate immunity. Here, we used the evolutionary trace approach based on phylogenetic information to predict the evolutionary epitope of Spätzle and found that it mainly clusters in several adjacent loops of Spätzle far from the cystine-knot structural domain. We designed six mutants of Spätzle based on the evolutionary epitope and transfected them into a stable cell line expressing the luciferase reporter gene under the control of the drosomycin promoter. Luciferase assays showed that these mutants cannot significantly activate the drosomycin promoter, suggesting the involvement of these sites in binding of Spätzle to the Toll receptor. These data highlight the importance of the Trp-loop of the mushroom-shaped Spätzle dimer in Toll receptor activation and demonstrate that evolution-guided site-specific mutagenesis represents a useful and promising strategy for understanding the ligand-receptor interaction.